Eksistensi Media Sosial dalam Meningkatkan Motivasi Belajar Santri - Ahmadi (AL-FIKRAH: Jurnal Studi Ilmu Pendidikan dan Keislaman, 2018)
Social Media is a new phenomenon that can not be avoided its devepoment. The rising of using social media was been penetrating to various circles, especially among juveniles. The use of social media has become very popular among juveniles, it’s used without considering the good and bad. While social media also has a lot of negative impacts besides its many positive impacts. So that, it needs to give attention for them. Because, someone who used social media excessively and without controlling, that case able to be each factor of the occurence something that are not desirable. Like the inclusion of the influence of westernization on the interaction of juveniles, this influence can damage the social and religious order. Thus, Pesantren education becomes the solution towards the appearance of this problem. Because the characteristics of Pesantren (islamic boarding schools) capable of providing comprehensively supervision of the students. Pesantren not only offers intellectual education but also moral education (character) that’s integrated into the souls of the students.